The Role and Contribution of Islamic Economic Thought to the Development of Modern Economics - Rizki Ananda; Retri Dwi Puspitasari; Siradjuddin (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence and contribution of Islamic economic thought on the development of modern economics from theoretical, practical, and philosophical aspects. The research method used is descriptive qualitative through library research, by reviewing classical and contemporary literature relevant to Islamic economic theory, its historical development, and its application in the global economic context. The results of the study indicate that Islamic economic thought plays a significant role in forming the foundation of modern economic theory through the concept of equitable wealth distribution, stable and inclusive Islamic financial principles, and the application of business ethics based on the values of honesty, justice, and social responsibility. In addition, Islamic economic instruments such as zakat, waqf, sukuk, and microfinance institutions have proven effective in addressing inequality, increasing financial inclusion, and promoting sustainable development. These findings emphasize that the integration of Islamic values in the global economic system is not merely a normative alternative, but a strategic necessity in creating a just, inclusive, sustainable, and welfare-oriented economic order.